Blinatumomab in pediatric B-acute lymphoblastic leukemia - Yifang Cheng; Aiguo Liu (Frontiers in Immunology)
Blinatumomab, a bispecific T-cell engager, has demonstrated substantial clinical benefits in treating pediatric patients with relapsed or refractory B-cell acute lymphoblastic leukemia (R/R B-ALL). Approved by FDA for several indications, blinatumomab is now integral to therapeutic protocols for specific pediatric cohorts, with real-world applications steadily increasing. As one of the representatives of cutting-edge immunotherapy for pediatric ALL, blinatumomab plays a crucial role in precision medicine against the backdrop of current genetic testing. Clinical efficacy is influenced by factors such as tumor burden, endogenous T-cell function, CD19 antigen loss, and lineage switch. Treatment-related complications, such as cytokine release syndrome (CRS), neurotoxicity (ICANS), and infections, necessitate vigilant monitoring. Administration involves continuous intravenous infusion, with consideration for drug interactions. Despite proven short-term efficacy and tolerability, long-term impacts on pediatric patients warrant further investigation. Current studies refine dosing strategies and combinational approaches to enhance therapeutic precision for pediatric patients. This review synthesizes selected literature related to clinical trials of blinatumomab, emphasizing determinants of clinical efficacy and adverse events associated with treatment.